Developing index competency for the Malaysian tourism and hospitality graduates - Mohd Shariff, Nurhazani; Zainol Abidin, Azlan; Kayat, Kalsom; Zainol, Noor Azimin (American Scientific Publishers, 2015)
Various models have been developed for the purpose of identifying graduates competencies. However, such specific model has not been found in the context of Malaysian tourism and hospitality education.This study develops an index competency for the Malaysian tourism and hospitality graduates through the perspectives of the industry.The process of developing the index consisted of three major stages—items generation, items verification and items development.The developed index contributes to the planning and designing the tourism and hospitality program more effectively by taking into consideration the competencies required by the industry. Hence it also assists the graduates to survive within the industry as they possess what the industry wants.